An Affordable In-house Tubular Retractor for Evacuation of Intracerebral Hematomas: A Case Series and Literature Review - Kaewborisutsakul, Wilairat K.; Kaewborisutsakul, Anukoon; Chatpun, Surapong; Oungbho, Kwunchit; Srakhao, Waritorn; Sungkaro, Kanisorn; Taweesomboonyat, Chin (Journal of Neurological Surgery Reports, 2025)
Intracerebral hemorrhage (ICH) disproportionately affects low- and middle-income countries (LMICs), where prevalence and outcomes are poor. Surgical intervention is often necessary in life-threatening cases. This study explored the feasibility of using a low-cost, in-house tubular retractor for ICH evacuation in a resource-limited setting.We retrospectively reviewed adults with spontaneous supratentorial ICH who underwent evacuation with an International Organization for Standardization (ISO)-compliant, in-house tubular retractor (production cost approximately $60) between January 2023 and June 2024. Outcomes included hematoma volume reduction, correction of midline shift, perioperative complications, reoperation, hospital stay, and Glasgow Coma Scale (GCS) scores at discharge and 6 months.A total of 18 patients (13 males, 5 females; mean age 60.6 ± 13.8 years) underwent surgery. Median hematoma volume was 65.3 cm3 (IQR, 48.5–93.8), with a mean reduction of 81.2% ± 11.7 (median 83.9% [IQR 73.4–88.3]). Midline shift correction averaged 58.5% ± 28.0 (median 55.9% [IQR 43.7–69.6]). Hematoma evacuation was similar whether surgery occurred within 6 hours or later (79.8% vs. 83.5%, p = 0.49). Putaminal and frontal hematomas (n = 14) showed greater reduction than non-putaminal (n = 4), though not statistically significant. Median hospital stay was 23.5 days (IQR, 14.5–50.5). At 6 months, median GCS improved from 13 (IQR, 9–14) at discharge to 15 (IQR, 12–15). Two patients died of non-neurological causes.Use of an in-house, ISO-compliant tubular retractor is feasible and cost-effective for intracerebral hematoma evacuation in resource-limited settings. These preliminary findings support further investigation to refine the technique and assess its clinical impact.
Keywords: stroke; tubular retractor; endoport; minimal invasive surgery